Upaya Mahasiswa KKN UINSU 2025 dalam Menumbuhkan Moderasi Beragama pada Sikap Toleransi di Desa Besadi melalui Gebyar Kreasi dan Seni - Muhammad Akbar Rosyidi Datmi; Ucok Kurnia Meliala Hasibuan; Putri Alisia Silaen; Sapna Tanjung; M Ridhotullah Rizki Nafis; Nia Putri Ramadhani Polem; Raihan Ramadhansyah; Febry Ardiansyah Siregar; Dinda Monica Sari; Mara Halim (Jurnal Pengabdian Masyarakat, 2025)
This study aims to explore the efforts of students from the Community Service Program (KKN) at the State Islamic University of North Sumatra (UINSU) in fostering religious moderation and tolerance in Besadi Village through the Creative Arts Festival (Gebyar Kreasi dan Seni). Religious moderation is seen as a crucial foundation for building a harmonious community amidst religious and cultural diversity. KKN students act as agents of social change, introducing the values ​​of religious moderation through creative activities such as art performances, cultural competitions, and interfaith dialogues, presented in an educational and inclusive manner. This study used a qualitative approach with descriptive methods, collecting data through interviews, participant observation, and documentation. The results indicate that the Creative Arts Festival (Gebyar Kreasi dan Seni) successfully raised awareness among the Besadi Village community about the importance of religious moderation and strengthened tolerance among residents. This activity also served as an effective means of strengthening social ties between residents through diverse artistic and cultural expressions. However, challenges such as differing views and a lack of community participation still require attention. This research is expected to serve as a reference in developing diverse moderation programs based on arts and cultural activities in rural areas.